STUDENT’S SELF-REGULATORY SKILLS AS CORRELATE OF THEIR ACADEMIC ACHIEVEMENT IN BIOLOGY IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of STM Education, 2025)
Students need for self-regulatory skills for academic success, personal growth and future career has been underscored. Various studies focus on different aspect of self-regulation but the applicability, implementation and nexus with self-efficacy and motivation, as integral skills for success in biology remain pertinent. Therefore, the study examined self-regulatory skills (self – efficacy and motivation) as correlate of students’ academic achievement in Biology in public secondary schools in Anambra State. Two research questions and Two Hypotheses tested at 0.05 level of significance guided the study.  Correlational research design was adopted for the study. The population of the study comprise 8,019 SS2 students drawn from 94 Public secondary schools in Awka and Otuocha education zone in Anambra State Post Primary school service commission Awka.  A total of 637 SS2 Biology students formed the respondents for the study and were drawn using simple random sampling technique. Students’ self-regulatory skills   scale (SSRSS) and Student's Biology Interest Scale (SBIS) validated at a reliability coefficient of 0.86 and 0.79 respectively served as instruments. Cronbach Alpha was used to test for the consistency of the reliability of the instruments. Pearson’s Product Moment correlation coefficient was used to answer the research questions. t-Test correlation was used to test hypotheses 1 and 2. The findings of the study revealed that there was low positive correlation between self – efficacy skill on academic achievement. There was low positive correlation between motivation skill on academic achievement. The relationships were not statistically significant. Students should practice self-reflection to identify their area of strength and weakness in biology subject to promote self-regulatory skills. The study recommended among others that teachers should incorporate activities that promote self-efficacy and problem -solving skills such as setting achievable goals and providing feedback. Students should inculcate the mindset of achieving a set goal for learning biological concepts in order to boost their interests and achievement.